2022
DOI: 10.3390/pr11010011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Processing Conditions on the Supercritical Extraction and Impregnation of Rosemary Essential Oil in Linear Low-Density Polyethylene Films

Abstract: The supercritical fluid extraction of essential oil from rosemary leaves and its subsequent impregnation in linear low-density polyethylene (LLDPE) films were studied. The effects of temperature (318 and 338 K), pressure (15 and 25 MPa) and rosemary particle size (0.9 and 0.15 mm) on the extraction yield were investigated. Impregnation assays were developed at two different values of pressure (12 and 20 MPa), temperature (308 and 328 K), and impregnation time (1 and 5 h). The extraction yield of rosemary essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 88 publications
1
3
0
Order By: Relevance
“…It was found that the effect of pressure increase on the nucleation and growth rates has been overcome. Similar results have been observed in the articles by Sodeifian et al 64 , Esfandiari et al 65 , Honarvar et al 19 , and Reverchon et al 66 regarding the effects of pressure and temperature on particle diameter. It is worth mentioning that Hezave et al 67 , 68 observed different results regarding the effect of temperature and pressure when micronizing Fenoprofen (C 15 H 14 O 3 ) and Ketoprofen (C 16 H 14 O 3 ) drug particles.…”
Section: Resultssupporting
confidence: 88%
“…It was found that the effect of pressure increase on the nucleation and growth rates has been overcome. Similar results have been observed in the articles by Sodeifian et al 64 , Esfandiari et al 65 , Honarvar et al 19 , and Reverchon et al 66 regarding the effects of pressure and temperature on particle diameter. It is worth mentioning that Hezave et al 67 , 68 observed different results regarding the effect of temperature and pressure when micronizing Fenoprofen (C 15 H 14 O 3 ) and Ketoprofen (C 16 H 14 O 3 ) drug particles.…”
Section: Resultssupporting
confidence: 88%
“…A detailed explanation of the solubility in scCO 2 measurement is documented elsewhere [39, 66–72], and a brief explanation of this process is provided in the Supporting Information file. The solubility of mebeverine in scCO 2 is expressed as mole fraction and in kg m −3 .…”
Section: Methodsmentioning
confidence: 99%
“…The level of such solubility determines the role of scCO 2 in the supercritical process being considered (whether to use it as solvent, antisolvent, or reaction medium). For instance, processes involving rapid expansion of supercritical solution (RESS) may be used to prepare nanoparticles of drugs that have high solubility in scCO 2 [7], while methods such as supercritical antisolvent (SAS) [8][9][10][11], gas antisolvent [12][13][14], solution-enhanced dispersion by SCFs [15][16][17][18], aerosol solvent extraction system [19][20][21][22], and supercritical solvent impregnation techniques [23][24][25], may be considered for drugs that have low solubility in scCO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Quite recently, several studies have investigated the incorporation of volatile and non-volatile bioactive compounds in polymer films using the supercritical solvent impregnation technique [23][24][25][26]. The impregnation is normally performed under mild heating conditions (temperatures up to 55 • C); however, the use of supercritical fluids requires additional processing steps, and the bioactivity and mechanical properties of the obtained films are highly dependent on the processing conditions [27].…”
Section: Introductionmentioning
confidence: 99%